Olfactory Dysfunction in Mental Illness - Marin, Concepció; Alobid, Isam; Fuentes, Mireya; López-Chacón, Mauricio; Mullol, Joaquim (Current allergy and asthma reports, 2023)
Purpose of Review Olfactory dysfunction contributes to the psychopathology of mental illness. In this review, we describe the neurobiology of olfaction, and the most common olfactory alterations in several mental illnesses. We also highlight the role, hitherto underestimated, that the olfactory pathways play in the regulation of higher brain functions and its involvement in the pathophysiology of psychiatric disorders, as well as the effect of inflammation on neurogenesis as a possible mechanism involved in olfactory dysfunction in psychiatric conditions. Recent Findings The olfactory deficits present in anxiety, depression, schizophrenia or bipolar disorder consist of specific alterations of different components of the sense of smell, mainly the identification of odours, as well as the qualifications of their hedonic valence (pleasant or unpleasant). Epidemiological findings have shown that both environmental factors, such as air pollutants, and inflammatory disease of the upper respiratory tract, can contribute to an increased risk of mental illness, at least in part, due to peripheral inflammatory mechanisms of the olfactory system. Summary In this review, we describe the neurobiology of olfaction, and the most common olfactory function alterations in several psychiatric conditions and its role as a useful symptom for the differential diagnosis. We also highlight the effect of inflammation on neurogenesis as a possible mechanism involved in olfactory dysfunction in these psychiatric conditions.